Ion-Pair Extraction-Spectrophotometric Determination of Trace Amounts of Minoxidil - ATTARAN, A.M.; PARHAM, H. (Asian Journal of Chemistry, 2010)
A simple, sensitive and selective extraction-spectrophotometric method for the determination of trace amounts of minoxidil is reported. The minoxidil-orange-II ion pair in acidic media is quantitatively extracted into dichloromethane and its absorbance is measured at 482 nm at room temperature. The effect of different variables such as solvent, volume of extracting solvent, volume of anionic reagent, pH, ionic strength (NaCl 0.1 M) and shaking time is investigated and optimum conditions for quantitative extraction of minoxidil is obtained. Calibration graph is linear over the minoxidil concentration range of 0.3-6.0 μg mL-1 and a regression coefficient of 0.9974 is obtained. The relative standard deviation of 8 replicate determination of 3.0 μg mL-1 of minoxidil is 3.54 %. Limit of detection of the method is 43.2 ng mL-1. The method is used for determination of minoxidil in 5 % solution and also mixture solution of minoxidil and tertinoin and good results are obtained.